The War Planners Series : Books 1-3 - Watts, Andrew (Novelist) ([United States] : Point Whiskey Publishing, 2017)
"A nation on the brink of war. A conspiracy that threatens the globe. And one military family, caught in the middle, fighting for freedom. The war planners series: Books 1-3 includes the first three books in the war planners series" --Page [4] cover
Keywords: United States. -- Central Intelligence Agency -- Fiction; Terrorism -- Prevention; Fiction; Terrorists -- Fiction; Intelligence officers -- Fiction; Technologists -- Fiction; Cyberinfrastructure -- Fiction; Conspiracies -- Fiction; Missing persons -- Fiction; China -- Fiction; Fiction